PERANAN SIKOLA BUDAYA TOBONGA DALAM PENGEMBANGAN KARAKTER REMAJA DI DESA BONTO SALAMA KECAMATAN SINJAI BARAT KABUPATEN SINJAI - Hajar, Nurfahmi; Sailan, Manan; Agus, Andi Aco (Jurnal Tomalebbi, 2024)
This research aims to: (1) Find out strategies for developing adolescent character in Tobonga Cultural School activities in Bonto Salama Village. (2) Describe the character values developed in teenagers in the Tobonga Cultural School activities in Bonto Salama Village. This research approach is descriptive with a qualitative research type. The data sources for this research consist of primary data sources, namely data obtained directly from informants and secondary data sources, namely data obtained through literature study. Data collection techniques are carried out through observation, interviews and documentation. Data analysis was carried out by data reduction, data presentation and drawing conclusions. Meanwhile, checking the validity of the data uses triangulation techniques.The results of the research show that: (1) The strategy for developing adolescent character in Tobonga Cultural Sikola activities is gathering and discussing together, theater performances, natural schools, as well as exemplary and habituation methods. (2) The character values developed in teenagers after participating in the Tobonga Culture Sikola activities are self-confidence, cooperation, caring for others and the environment, love for local culture and responsibility.